2014
DOI: 10.1159/000366403
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Increases Gap Junctional Communication in Epithelial Cells

Abstract: Background/Aims: The finding that endogenous ouabain acts as a hormone prompted efforts to elucidate its physiological function. In previous studies, we have shown that 10 nM ouabain (i.e., a concentration within the physiological range) modulates cell-cell contacts such as tight junctions and apical/basolateral polarity. In this study, we examined whether 10 nM ouabain affects another important cell-cell feature: gap junction communication (GJC). Methods: We employed two different approaches: 1) analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Our previous findings, that 10 nM ouabain triggers a quick enhancement of GJIC, plus the fact that this response is not impaired by inhibitors of RNA or protein synthesis [44] suggest that no synthesis of connexins are required to achieve this effect. To test this (A) Cell lysates were prepared from MDCK monolayers, either control or incubated with 10 nM ouabain for 1 hour, then equal amounts of total cell protein were subjected to SDS-PAGE and western blotting with antiCnx43 antibodies.…”
Section: Ouabain Does Not Promote Synthesis Of Cnx43mentioning
confidence: 80%
See 3 more Smart Citations
“…Our previous findings, that 10 nM ouabain triggers a quick enhancement of GJIC, plus the fact that this response is not impaired by inhibitors of RNA or protein synthesis [44] suggest that no synthesis of connexins are required to achieve this effect. To test this (A) Cell lysates were prepared from MDCK monolayers, either control or incubated with 10 nM ouabain for 1 hour, then equal amounts of total cell protein were subjected to SDS-PAGE and western blotting with antiCnx43 antibodies.…”
Section: Ouabain Does Not Promote Synthesis Of Cnx43mentioning
confidence: 80%
“…As part of our interest in the effect that ouabain, in a nanomolar range, has on epithelial (MDCK) cells, we evaluated in a previous work, how it influences gap junctional intercellular communication (GJIC) by dye transfer assays and by electrical capacitance measurements [44]. We found that it, triggers an enhanced GJIC response, that is significantly noticeable from 10 minutes after addition of ouabain to the bathing media and reaches a maximum at about one hour, followed by a slow decaying, then a sustained response that last, al least 24 hrs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of connexins can depend on the physiological state, including hibernation, arousal, level of hormone and mechanical environments [34][35][36]. Several studies demonstrated that Cx43 was increased in ECs cultured alone by high laminar shear stress (15 dyn/cm 2 ) compared to static conditions [19,37].…”
Section: Discussionmentioning
confidence: 99%